TEXTUAL FUNCTION VARIATIONS OF FOREIGN EMBASSIES' PRESS RELEASES AND THEIR IMPLICATIONS FOR TRANSLATION TEACHING - Amalia, Chusna; Tou, Asruddin Barori (LingTera, 2016)
There are three purposes of this research; first, to describe the textual function variations of foreign embassies' press releases; second, to describe the contextual motivating factors of the textual function variations of foreign embassies' press releases; and third, to describe the implications of the textual function variations of foreign embassies' press releases for translation teaching. This research used quantitative and qualitative approaches. The result shows that the global overall textual function variation of the translational texts is very low which is represented by the mean of 1.25. In other words, the difference between Text 1 in Bahasa Indonesia (T1) and Text 2 in English (T2) is not significant. The contextual motivating factors of the textual function variations are analyzed from the translational texts' mode and the clauses' themes. The mode is written, realized through graphic channel therefore there is a high level of formality. The most occurring theme is subject which shows that the translators put emphasis heavily on the actor or the goal of the message in the clause. The most frequent pattern of thematic progression is repetition which efficiently constructs a communicative press release. The implications for translation teaching are these successful translational texts can be used in a more profitable manner as documentary sources for translation teaching.